Human capital, cultural values and economic performance in European regions - Mikko Weckroth; Teemu Kemppainen (Regional Studies, Regional Science, 2016)
This study examines the cross-sectional association of three value orientations (self-direction, achievement and power) and level of gross domestic product (GDP) in 289 NUTS regions. Regional value aggregates, drawn from Schwartz’s Human Value Scale included in the European Social Survey, are taken to indicate value-based human capital. Regression analysis shows that self-direction, indicating independent thought, action and creativity, is a strong predictor for regional GDP after controlling for standard control variables and spatial autocorrelation. Additionally, analysis implements welfare regimes as indicators of larger socio-historic frames and finds significant geographical variations within these frames regarding the relationship between prevailing value climate and level of economic performance. The study contrasts perspectives from economic geography and cultural studies to the literature on alternative definitions and measures for human capital and argues that a synthesis of these perspectives can enrich one’s understanding of the economic geography in Europe.